2016
DOI: 10.1038/srep36251
|View full text |Cite
|
Sign up to set email alerts
|

Strontium inhibits titanium particle-induced osteoclast activation and chronic inflammation via suppression of NF-κB pathway

Abstract: Wear-particle-induced chronic inflammation and osteoclastogenesis have been identified as critical factors of aseptic loosening. Although strontium is known to be involved in osteoclast differentiation, its effect on particle-induced inflammatory osteolysis remains unclear. In this study, we investigate the potential impact and underling mechanism of strontium on particle-induced osteoclast activation and chronic inflammation in vivo and in vitro. As expected, strontium significantly inhibited titanium particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 37 publications
(86 reference statements)
2
50
0
1
Order By: Relevance
“…The presence of Sr 2+ ‐substituted biphasic calcium phosphate particles decreased the production of TNFα, IL‐6 and IL‐8 in LPS‐stimulated monocytes. Additionally, a new animal study suggested that Sr 2+ significantly inhibited titanium particle‐induced inflammatory infiltration and bone loss via suppression of the nuclear factor‐kappaB pathway in a murine calvarial osteolysis model . We thus hypothesized that Sr 2+ could induce an anti‐inflammatory and an anti‐osteoclastogenic effect, implying it has a therapeutic effect for periodontitis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The presence of Sr 2+ ‐substituted biphasic calcium phosphate particles decreased the production of TNFα, IL‐6 and IL‐8 in LPS‐stimulated monocytes. Additionally, a new animal study suggested that Sr 2+ significantly inhibited titanium particle‐induced inflammatory infiltration and bone loss via suppression of the nuclear factor‐kappaB pathway in a murine calvarial osteolysis model . We thus hypothesized that Sr 2+ could induce an anti‐inflammatory and an anti‐osteoclastogenic effect, implying it has a therapeutic effect for periodontitis.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, a new animal study suggested that Sr 2+ significantly inhibited titanium particle-induced inflammatory infiltration and bone loss via suppression of the nuclear factor-kappaB pathway in a murine calvarial osteolysis model. 28 We thus hypothesized that Sr 2+ could induce an anti-inflammatory and an anti-osteoclastogenic effect, implying it has a therapeutic effect for periodontitis. These findings are essential for the application of Sr 2+ in periodontitis and periodontal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The RAW264.7 cells were plated in 24-well plates in triplicate and transfected with an NF-kB and NFATc1 luciferase reporter construct, as described. (33,35) Briefly, the cells were cultured for 24 hours and then stimulated with RANKL (50 ng/mL), JWH133 (1mM), or SR144528 (100nM) for 8 hours. After that, the cell lysates were isolated and luciferase activity was measured using a dual-luciferase reporter assay system.…”
Section: Luciferase Assaymentioning
confidence: 99%
“…We found that co-cultured Ti with Al-NPs could slightly inhibit the degradation of the NF-kB inhibitory subunit IκBα and suppressed the activation NF-kB. What' more, it lightly reduced the generation of inflammatory mediators 41,51 . And with our further study, we found that the Al signifiganct prevented the IL-1β expression ( # p < 0.05) via attenuating the NF-kB signaling activator β-TRCP and reducing the expression of Casepase-3 ( Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Bortezomib (BTZ), which is one of the reversible proteasome inhibitors, has been shown to be a potent inhibitor of NF-κB 38,39 . Bortezomib could block the nuclear transport of NF-kappaB, mainly by inhibiting the chymotryptic activity of polyubiquitinated protein degradation in 26S proteasome 30,[40][41][42][43] . Bortezomib at the first has been approved by FDA as a drug for the therapy of tumor, but it is now also considered as a remedy for non-tumorous diseases such as inflammation diseases [44][45][46] .…”
mentioning
confidence: 99%